Team functioning across different tumour types: Insights from a Swiss cancer center using qualitative and quantitative methods - Felicitas Hitz; Karin Ribi; Gudela Grote; Michaela Kolbe; Christof Schmitz; Benjamin W. Lamb; Thomas Ruhstaller; Peter Berchtold; Nick Sevdalis (Cancer Reports, 2022)
Abstract Background Multidisciplinary care is pivotal in cancer centres and the interaction of all cancer disease specialists in decision making processes is state‐of‐the‐art. Aim To describe differences of MDTMs by tumour type. Methods Twelve multidisciplinary team meetings (MDTMs) with participation of different cancer disease specialists at a tertiary hospital were assessed by an exploratory sequential mixed method approach with interviews, observations and a survey to address the following five topics: organisational structure and supporting technology; leadership; teamwork; decision‐making, perceived value and motivation. Thirteen persons with different tumour specialities and levels of seniority were interviewed. The 12 MDTMs were observed twice by uninvolved persons and evaluated by the participating physicians with a survey. Results There were no systematic differences between MDTMs for different tumour types with the exception of the non‐disease specific type MDTM, which was the only one for which the organisational structure was not driven by an electronic tool. However, several factors could be identified that generally influenced the functioning of the MDTMs. In particular, the quality of decision‐making was highly dependent on the availability of case‐based information and the presence of relevant cancer disease specialists. Leadership and teamwork were rated as important and were comparable across the MDTM. Team participants' motivation and perceived value of MDTMs was high across all meetings. Conclusion MDTM at a single institution did not demonstrate disease specific characteristics. An effective MDTM, irrespective of the tumour type, can be successfully structured by technical means and a chairperson coordinating the interaction of cancer disease specialists to improve the decision‐making process.